Identifiación del potencial aprovechable de los residuos sólidos orgánicos que se generan en mercados, supermercados, parques, jardines y diferentes sectores industriales de la Zona Sur del Distrito Metropolitano de Quito. - Alvaro Gualoto, Madeleine Estefanía (2013)
In the Metropolitan District of Quito about 1800 tons per day of waste is generated, of which organic solid waste equivalent to 62% of all municipal solid waste generated in the district, with per capita output 0.84 kg / person / day. The objective of this research was to obtain data generation RSO markets, supermarkets, parks, gardens and various industrial sectors of the southern part of the Metropolitan District of Quito.